Do asthma patients with panic disorder really have worse asthma? A comparison of physiological and psychological responses to a methacholine challenge. Issue 10 (October 2015) - Boudreau, Maxine; Lavoie, Kim L.; Cartier, André; Trutshnigg, Barbara; Morizio, Alexandre; Lemière, Catherine; Bacon, Simon L.
Abstract: Background: Panic disorder (PD) has been linked to worse asthma outcomes. Some suggest that asthmatics with PD have worse underlying asthma; others argue that worse outcomes are a result of their tendency to over-report symptoms. This study aimed to measure physiological and psychological responses to a simulated asthma attack (methacholine challenge test: MCT) in asthmatics with and without PD. Methods: Asthmatics with (n = 19) and without (n = 20) PD were recruited to undergo a MCT. Patients completed subjective symptom questionnaires (Panic Symptom Scale, Borg Scale) before and after a MCT. Physiological measures including heart rate (HR), and systolic and diastolic blood pressure (SBP/DBP) were also recorded. Results: Analyses, adjusting for age and sex, revealed no difference in methacholine concentration required to induce a 20% drop in forced expiratory volume in one second (FEV1 : F = 0.21, p = .652). However, PD patients reported worse subjective symptoms, including greater ratings of dyspnea (F = 8.81, p = .006) and anxiety (F = 9.44, p = .004), although they exhibited lower levels of physiological arousal (i.e., HR, SBP/DBP). An interaction effect also indicated that PD, relative to non-PD, patients reported more panic symptoms post-MCT (F = 5.05, p = .031). Conclusions: Asthmatics with PD report higher levels of subjective distress, despite exhibiting lower levels of physiological arousal, with no evidence of greater airway responsiveness. Results suggest that worse outcomes in PD patients may be more likely due to a catastrophization of bodily symptoms, rather than worse underlying asthma. Interventions designed to educate patients on how to distinguish and manage anxiety in the context of asthma are needed. Highlights: Asthmatics with PD report higher levels of subjective distress in response to a MCT. Asthmatics with PD do not exhibit greater airway responsiveness than no-PD patients. Worse outcomes in PD patients may be due to a catastrophization of bodily symptoms.